Dreaming of a Jewish Democracy: Sammy Gronemann as High Judge and Chief Architect of the Pre-State Zionist Judiciary (1911-1946) - Kühne, Jan (Naharaim, 2024)
This article explores the history of the pre-state Zionist judiciary, focusing on Sammy Gronemann's instrumental role as its high judge and chief architect from 1911 to 1946. In doing so, it addresses a significant gap in existing research. Despite extensive attention that has been paid to his contributions to German and Hebrew literature, Gronemann's legal profession and judicial endeavors within the World Zionist Organization (WZO) have been largely overlooked in academic discourse. To provide context and illuminate Gronemann's influential role, the first section of this article offers a concise historical account of the pre-state Zionist judiciary's genesis. The second section delves into Gronemann's disillusionment and suppressed critique of the WZO's democratization initiatives. This is evident in his private writings, including a hitherto unknown letter correspondence with Theodor Heuss, the first president of West Germany. The exploration undertaken unveils the moral authority of Gronemann as representative of the institutionalized Zionist conscience, a role he embodied as the chief judge and architect of the Zionist pre-state judiciary.